Zinc oxide nanowires and nanorods fabricated by vapour-phase transport at low temperature - Xu, Chunxiang (2012)
Using zinc chloride as source material, zinc oxide nanowires and nanorods were fabricated by a vapour-phase transport method at low temperature. The nanowires grown on gold-coated silicon showed a uniform diameter of about 40 nm, and the nanorods on copper-coated silicon grew upwards to form flower-like arrays. The x-ray diffraction and transmission electron microscopy analyses demonstrated that the nanostructural zinc oxide grew along the [0001] direction. The growth process was attributed to a vapour–liquid–solid mechanism. Distinct photoluminescent behaviours were observed for zinc oxide nanostructures grown on gold-coated and copper-coated silicon wafers.